Self-healing behavior of a polyelectrolyte-based lubricant additive for aqueous lubrication of oxide materials - Lee, S.; Müller, M.; Heeb, R.; Zürcher, S.; Tosatti, S.; Heinrich, M.; Amstad, F.; Pechmann, S.; Spencer, N.D. (Tribology letters, 2006)
We report on the self-healing behavior of a polyelectrolyte-based aqueous lubricant additive, poly(l-lysine)-graft-poly(ethylene glycol) (PLL-g-PEG), during aqueous lubrication of an oxide-based tribosystem. Combined pin-on-disk tribometry and fluorescence microscopy experiments have shown that stable lubricating performance was enabled by means of rapid healing of the worn tribopair surface by polymers dissolved in the adjoining bulk lubricant. This rapid ‘self-healing’ of PLL-g-PEG is attributed to electrostatic interactions between the polycationic poly(l-lysine) (PLL) backbone of the polymer and negatively charged oxide surface. In contrast, a similar healing effect was not readily achievable in the case of methoxy-poly(ethylene glycol)-trimethylsilylether (Sil-PEG), a lubricant additive that is covalently bonded to the surface prior to tribological stress.